PENGARUH VARIASI PROPILENGLIKOL TERHADAP FORMULASI DAN KARAKTERISTIK SEDIAAN HAIR TONIC EKSTRAK DAUN JAMBU AIR SEMARANG (Syzygium aqueum (Burm.f.)) - Herdiana, Irvan; Setiawati, Tia; Rubiyanti, Rani (Poltekkes Kemenkes Bandung, 2024)
Hair loss as a factor of baldness is a problem that worrying for everyone. The contains of wax apple (Syzygium aqueum (Burm.f.)) leaves are flavonoids/polyphenols, alkaloids, saponins, and tannins which are known have benefits for hair. The use of hair tonic is efficient in treating hair loss. The purpose of this study was to determine the effect of variations in propylenglycol on the formulation and characteristics of the hair tonic preparation extract of wax apple leaves. The method used is experimental laboratory with descriptive statistical analysis. The extract of wax apple was carried out using infusion method. The extract is formulated into 3 formulas with variations of propylenglycol. Testing of characteristic hair tonic extract of wax apple leaves includes organoleptic, pH, homogeneity, specific gravity, and viscosity. The results showed that the hair tonic was clear yellow, had good homogenity, pH 5.1-5.8, specific gravity 0.925-0.957, and viscosity 1.299-1.61 centipoise. The effect of variation in propylenglycol are the increasing of pH, specific gravity and viscosity which are has in accordance with SNI requirements.